Dampak Pembimbing Khusus pada Pelaksanaan Haji Reguler di Kota Banda Aceh - Fakhruddin Lahmuddin (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to analyze the impact of Special Hajj Guides (PKH) on the implementation of the regular Hajj in Banda Aceh, particularly in enhancing pilgrims’ mental preparedness, understanding of Hajj rituals, and the smooth conduct of the Hajj. This study analyzes the impact of PKH on the implementation of the regular Hajj in Banda Aceh, specifically in improving pilgrims’ mental preparedness, understanding of Hajj rituals, and the smoothness of the pilgrimage. Using a qualitative field research approach, the study analyzed scientific literature, policies from the Ministry of Religious Affairs, and Banda Aceh Hajj reports. The results indicate that PKH has a tangible impact on supporting the implementation of the regular Hajj, both from a spiritual and administrative perspective. On the spiritual side, PKH serves as a Hajj ritual guide and religious facilitator capable of enhancing the mental preparedness of pilgrims, deepening their understanding of Hajj jurisprudence, and fostering inner peace throughout the performance of the Hajj rituals. This role becomes increasingly significant for elderly pilgrims, where the PKH also functions as a psychological companion who helps reduce anxiety, boost self-confidence, and maintain order and devotion during worship. Meanwhile, on the administrative side, the PKH serves as a mediator and service facilitator who assists pilgrims in understanding procedures, managing documents, and ensuring smooth coordination with various relevant parties. In this context, the role of the PKH also reflects the implementation of sharia-based service quality through an adaptive approach to the dimensions of tangibles, reliability, and empathy, thereby enabling the provision of more responsive and needs-oriented services to pilgrims. Thus, the Special Hajj Guide (PKH) plays a strategic role and has a significant impact in supporting the successful execution of the regular Hajj. This role is reflected in two main dimensions: spiritual and administrative.